Ellipsometric Studies on Silver Telluride Thin Films - M. Pandiaraman; N. Soundararajan; C. Kumar; R. Ganesan (Журнал нано- та електронної фізики)
Silver telluride thin films of thickness between 45 nm and 145 nm were thermally evaporated on well cleaned glass substrates at high vacuum better than 10 – 5 mbar. Silver telluride thin films are polycrystalline with monoclinic structure was confirmed by X-ray diffractogram studies. AFM and SEM images of these films are also recorded. The phase ratio and amplitude ratio of these films were recorded in the wavelength range between 300 nm and 700 nm using spectroscopic ellipsometry and analysed to determine its optical band gap, refractive index, extinction coefficient, and dielectric functions. High absorption coefficient determined from the analysis of recorded spectra indicates the presence of direct band transition. The optical band gap of silver telluride thin films is thickness dependent and proportional to square of reciprocal of thickness. The dependence of optical band gap of silver telluride thin films on film thickness has been explained through quantum size effect.